Criminalization of Sexual Acts in Jordanian Law (Comparative Study) - Issa, Hamzeh Abu; Al-Taraira, Mohammad (International Journal of Criminology and Sociology, 2021)
This article aimed to clarify the opinion of the Jordanian legislator regarding the criminalization of sexual acts in comparison to the position of the monotheistic religions and contemporary laws, in addition to knowing the Jordanian society’s view of criminalizing sexual acts. By looking at the Jordanian legal texts related to the subject, it became apparent to researchers that the Jordanian legislator adopts the principle of sexual freedom like other legislators in other countries, despite this violation of Islamic law, which is the official religion of the state according to the Jordanian constitution. In order to achieve the objectives of the study, the researchers adopted the descriptive and analytical approach that reads the opinion of the Jordanian legislator, the monotheistic religions, and contemporary laws in criminalizing sexual acts. Using the results of a questionnaire designed for the purpose of knowing the views of the Jordanian society on the principle of sexual freedom. This questionnaire was distributed to a random sample of 1000 people. The article reached a number of conclusions, including that (84)% of Jordanian society do not accept sexual freedom for religious, moral and social reasons. In light of the results of the article, the authors recommended abolishing the principle of sexual freedom from Jordanian law and calling on the Jordanian legislator to reconsider texts related to the criminalization of sexual acts in line with the culture of society.